Stephen Sykes and the Essence of Christianity - Avis, Paul (Ecclesiology, 2019)
Stephen Sykes chastised English (especially Anglican) theology for its neglect of systematic and doctrinal theology and worked for its revival. He viewed the liberal tendency in English theology in the 1960s and 1970s as attributable, at least in part, to lack of doctrinal rigour and to ecclesiastical woolliness. Sykes contributed to methodological reflection on systematic theology, but his occasional forays into systematics were not his major efforts. However, one systematic theological topic to which Sykes made a significant contribution was the question of the essence of Christianity, which he pursued in critical dialogue with a galaxy of modern theologians. His account of the essence in relation to the external' and internal' aspects of Christianity is not satisfactory and his conclusion that the essence is an essentially contested concept' is disappointing. Nevertheless, his discussion sheds light on the problem and remains a stimulus and resource for further work on this topic.